Reconciling the Interpretation of Sufism and Sharia: Sheikh ‘Abd al-Ra’uf al-Singkili’s Views on Women’s Leadership (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2025)
This study examines the thought of Sheikh ‘Abd al-Ra’ūf al-Singkili in his efforts to reconcile two often perceived opposing dimensions of Islam, sufism (spiritual dimension) and sharia (legal dimension), particularly in the context of the issue of female leadership. As a prominent 17th-century scholar from Aceh, Sheikh ‘Abd al-Ra’ūf held significant authority in both fiqh and mysticism and was known for his integrative and moderate approach. Using a qualitative library research method, the study analyzes his primary work, Mir’āt al-Ṭullāb, along with supporting secondary literature. The findings reveal that Sheikh ‘Abd al-Ra’ūf did not dichotomize sufism and sharia but sought to harmonize them within a holistic Islamic framework. Regarding female leadership, he adopted a conciliatory stance, neither outrightly rejecting nor fully endorsing it, choosing instead a contextual and moderate interpretation, also informed by contemporary fatwas from Haramayn scholars.Penelitian ini membahas pemikiran Syekh ‘Abd al-Ra’ūf al-Singkili dalam merekonsiliasi dua dimensi utama ajaran Islam tafsir tasawuf (spiritual) dan syariat (hukum) terutama terkait isu kepemimpinan perempuan. Sebagai ulama berpengaruh di Aceh abad ke-17, Syeikh ‘Abd al-Ra’ūf al-Singkili memiliki otoritas dalam fikih dan tasawuf serta dikenal karena pendekatannya yang moderat dan integratif. Menggunakan metode penelitian kepustakaan, penelitian ini menganalisis karya utama beliau, Mir’āt al-Ṭullāb, dan literatur pendukung lainnya. Hasilnya menunjukkan bahwa Syeikh ‘Abd al-Ra’ūf menolak dikotomi antara tasawuf dan syariat, serta mengedepankan harmoni dalam merespons isu-isu sosial-politik, termasuk kepemimpinan perempuan. Dalam hal ini, ia tidak memberikan dukungan atau penolakan secara mutlak, tetapi lebih pada posisi kompromis yang mempertimbangkan konteks zamannya, termasuk fatwa scholar Haramayn.